Data sharing policies and procedures model to improve public services delivery in local government - Nonchi, Samsu Bahari; Sidi, Fatimah; Ishak, Iskandar; Affendey, Lilly Suriani; Hanif Francis, Hasan Ganny; Hasan, Sirajuddin (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Accurate and adequate information is required in the decision making process before providing the services. These can be achieved by sharing of data among the data providers. This paper presents the investigation of the usability and the enhancement of the existing policies and procedures of data sharing for open data initiatives.